A quadripolar model of identity in adolescent foreign language learners - Taylor, Florentina (2011)
Integrating several psychological theories (e.g., self and identity, self-presentation and internalisation, possible selves and self-discrepancy, developmental processes in adolescence), this thesis proposes a new theoretical framework aiming to facilitate a better understanding of foreign language learning. The Quadripolar Model of Identity postulates the existence of four self components (private, public, ideal and imposed), whose pluridirectional interactions may lead to four types of self system (submissive, duplicitous, rebellious and harmonious) hypothesised to differ from one relational context to another (e.g., school, family, friends). For students, these identity processes are expected to fluctuate depending on the subject studied.